Stressful Presentations: Mild Cold Stress in Laboratory Mice Influences Phenotype of Dendritic Cells in Naïve and Tumor-Bearing Mice - Kokolus, Kathleen M.; Spangler, Haley M.; Povinelli, Benjamin J.; Farren, Matthew R.; Lee, Kelvin P.; Repasky, Elizabeth A. (Frontiers in Immunology, 2014)
The ability of dendritic cells to stimulate and regulate T cells is critical to effective anti-tumor immunity. Therefore, it is important to fully recognize any inherent factors which may influence DC function under experimental conditions, especially in laboratory mice since they are used so heavily to study immune responses. Physiological stress is well recognized to impair several arms of immune protection. The goals of this report are to briefly summarize previous work revealing how DCs respond to various forms of physiologically relevant stress and to present new data highlighting the potential for chronic mild cold stress inherent in mice housed at standard ambient temperatures required for laboratory mice to influence baseline DCs properties. Since recent data from our group shows that CD8+ T cell function is altered by mild chronic cold stress and since DC function is crucial for CD8+ T cell activation, we wondered whether mild cold stress may also be influencing DC properties. We found increased numbers of splenic DCs (CD11c+) in cold stressed mice compared to mice housed at a thermoneutral temperature, which significantly reduces cold stress. However, many of the DCs which are expanded in cold stressed mice express an immature phenotype. We also found that antigen presentation and ability of splenocytes to activate T cells were impaired compared to that seen in DCs isolated from mice at thermoneutrality. The new data presented here strongly suggest that the housing temperature of mice can affect fundamental properties of DC function which in turn could be influencing the response of DCs to added experimental stressors or other treatments.